Anesthetic Exposure in Staged Versus Single-Stage Cleft Lip and Palate Repair: Can We Reduce Risk of Anesthesia-Induced Developmental Neurotoxicity?. Issue 2 (8th March 2021) - Davila, Armando A.; Holzmer, Stephanie W.; Kubiak, Jeremy; Martin, Mark C.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Cleft lip and palate (CLP) repair is typically performed in a staged fashion, which requires multiple instances of anesthetic exposure during a critical period of infant neurodevelopment. One solution to this concern includes the implementation of a single-stage CLP repair performed between 6 and 12 months of age. This study aimed to compare total anesthetic exposure between single-stage and staged CLP repairs. A retrospective review of unilateral CLP repairs between 2013 and 2018 conducted at a single institution was performed. Patients underwent either traditional, staged lip and palate repair, or single-stage complete cleft repair, where palate, lip, alveolus, and nasal repair was performed simultaneously. Primary endpoints included: total surgical time and total anesthetic exposure. Secondary endpoints included: excess anesthesia time, recovery room time, length of stay, and type of anesthetic administered. Two hundred twenty-five (n = 225) unilateral CLP repairs were conducted at the Loma Linda University. Detailed anesthetic data for eighty-six (n = 86) single-stage and twenty-eight (n = 28) staged operations were available. There was a statistically significant decrease in anesthetic exposure in single-stage versus staged repairs (316 minutes versus 345 minutes, P = 0.017), despite similar procedure times (260 minutes versus 246 minutes, P = 0.224). This resulted in near double excess anesthetic exposure time in the staged group (98 minutes versus 56 minutes, P < 0.001), primarily occurring during induction. This analysis suggests that single-stage CLP repair can reduce wasted time under general anesthesia and potentially reduce harmful neuronal toxicity in the developmental period in this at-risk population.